Day-to-day Relationships between Physical Activity and Sleep Characteristics among People with Heart Failure and Insomnia. Issue 5 (3rd September 2021) - Ash, Garrett; Jeon, Sangchoon; Conley, Samantha; Knies, Andrea K.; Yaggi, Henry K.; Jacoby, Daniel; Hollenbeak, Christopher S.; Linsky, Sarah; O'Connell, Meghan; Redeker, Nancy S.
ABSTRACT: Objective: Examine the bidirectional relationships between within-person day-to-day fluctuations in physical activity (PA) and sleep characteristics among people with heart failure (HF) and insomnia. Participants: Ninety-seven community-dwelling adults [median age 61.9 (interquartile range 55.3, 70.9) years, female 41%] with stable HF and insomnia (insomnia severity index >7). Methods: This sub-study longitudinally analyzed 15 consecutive days and nights of wrist actigraphy recordings, that were collected for baseline data prior to participation in a randomized controlled trial of cognitive behavioral therapy for insomnia. We used two-level mixed models of within- (daily) and between-participants variation to predict daytime PA counts/minutes from sleep variables (total sleep time, sleep efficiency) and predict sleep variables from PA. Results: PA counts/minutes were low compared to prior cohorts that did not have HF (209 (166, 259)) and negatively associated with NYHA class (standardized coefficient βs  = −0.14, p < .01), age (βs  = −0.13, p = .01), comorbidities (βs  = −0.19, p < .01), and body mass index (βs  = −0.12, p = .04). After adjustment for all significant covariates, the within-participant association of total sleep time with next-day PA was estimated to be positive among participants with NYHA class II–IV HF (βs  = 0.09, p = .01), while the within-participant association of PA with same-night total sleep time was estimated to be positive among participants aged ≥60 years (βs  = 0.10, p = .03). Conclusions: Depending upon age and HF class, daytime PA was associated with longer same-night sleep and/or longer sleep was associated with greater next-day PA. Among those with more advanced HF, realistic sleep improvements were associated with clinically meaningful PA gains the next day.